Defenisi Etika Akademik - Ira Suryani; Pebrijah Nasution; Bunga Lestari; Juliana Juliana; Kesi Kesi; Nadia Haviza Purba (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2023)
Academic ethics refers to the rules or norms that govern ethical behavior in the academic world. Academic ethics includes values ​​held by the academic community, such as integrity, honesty, hard work, creativity, academic freedom, and social responsibility. Academic integrity is very important in academic ethics, because it involves honest and honorable intellectual skills and research skills. Intellectual skills include the ability to generate, collect, and analyze data, while research skills include the ability to plan, carry out, and publish high-quality research. Honesty and rigor are core values ​​of academic ethics, as they form the basis of research and teaching processes. Honesty means that academics must avoid fraud, plagiarism, and misuse of data, whereas thoroughness means that they must examine data carefully and ensure that the information they use is true and accurate. Creativity is also an important value in academic ethics, because academics are expected to produce original and innovative research and work. However, creativity must be carried out within an ethical framework and must not violate the values ​​of integrity and honesty. Academic freedom is also an important value in academic ethics, because it guarantees that academics can work independently and produce research and works that are not influenced by political or economic interests. However, academic freedom must be balanced with social responsibility, namely that academics must be responsible for the consequences of their research and teaching on society and the world. Overall, academic ethics is very important in the academic world, because it involves norms governing ethical behavior and maintaining integrity and honesty in the process of research and teaching. Keywords: academic ethics, Islamic education